Programmed death‐ligand 1 expression at tumor invasive front is associated with epithelial‐mesenchymal transition and poor prognosis in esophageal squamous cell carcinoma - Tsutsumi, Satoshi (Cancer Sci, 2017)
Programmed death‐ligand 1 (PD‐L1) plays a crucial role in the host immune system in cancer progression. The gene promoter region of PD‐L1 also contains a binding site for ZEB1, a transcription factor related to epithelial‐mesenchymal transition (EMT). The purpose of this study was to clarify the relationship between PD‐L1 and EMT and its clinical importance in esophageal squamous cell carcinoma (ESCC). PD‐L1 and ZEB1 expression at the tumor invasive front was examined by immunohistochemistry in resected specimens from 90 patients with ESCC who underwent surgery without preoperative therapy, and their expression and clinicopathological factors were compared. ZEB1 and PD‐L1 expression was determined in TE8 cells, which demonstrate the EMT phenotype, following ZEB1 knockdown by siZEB1. TE5, TE6 and TE11 cells with non‐EMT phenotype were also used for studies of TGF‐β1‐dependent EMT induction and ZEB1 and PD‐L1 expression. In cases of high PD‐L1 expression at the invasive front, significantly greater depth of tumor invasion, EMT, and less CD8(+) lymphocyte infiltration were observed. High PD‐L1 expression was also associated with worse overall and relapse‐free survival. A correlation was observed between PD‐L1 and ZEB1 expression. In TE8 cells, siZEB1 suppressed PD‐L1 and promoted E‐cadherin mRNA and protein expression. TGF‐β1 induced EMT and surface expression of PD‐L1 in TE5, TE6 and TE11 cell lines. PD‐L1 expression at the ESCC invasive front was related to ZEB1 expression, EMT and poor prognosis. We suggest that a cooperative mechanism bridging between tumor immune avoidance and EMT contributes to tumor malignancy in ESCC.